As políticas de educação inclusiva na perspectiva do ensino de surdos no município de Igarapé-Miri/PA - MELO, Rosileide de Jesus de Souza (Universidade Federal do Pará, 2025)
The debate on the issue of public policies for school “inclusion” is current and necessarily involves a broader reflection on the groups that have been located in the current discourses of social exclusion and a reflection on the issue of the right to education of groups that have been away from such a right. In this sense, this dissertation aimed to understand which “inclusive” educational public policies exist for the teaching of the deaf in the city of IgarapéMiri/PA. The research follows a qualitative approach (GÜNTER, 2006), as it is not our responsibility to make judgments, nor to allow concepts already formed to influence the research. Taking into account that data collection techniques must be aligned with the research strategy, we use document analysis as a technique (CELLARD, 2008; HELDER, 2006). The theoretical framework of the work is based on studies on the right to “inclusive” education for deaf people and on public policies that “include” these subjects, especially the international, national and local regulations; on public policies (CHRISPINO, 2016; DI GIOVANNI, 2009; MULLER; SUREAL, 2002); on studies on school “inclusion” of the Deaf (GESSER, 2009; STROBEL, 2009, 2018; VALSECCHI; MARTINS FILHO, 2020) among others. The Municipality, according to its regulations, has planned education to serve deaf students, and adhering to programs made available by the Ministry of Education (MEC) as a promoter of “inclusive” special education for the deaf. The data obtained show that the Municipality of Igarapé-Miri was awarded the “Inclusive” Education Program: Right to Diversity, Accessible School and Program, Implementation of Multifunctional Resource Rooms Program, Accessible School Transport Program and Direct Money at School Program – structure, accessibility and resource room. Such programs were crucial for the Municipality to structure its public policy for “inclusive” education for the deaf. The survey showed that compared to the number of schools in the Municipal education system, there are few schools that have Specialized Educational services in Igarapé-Miri. Therefore, the creation of new Multifunctional Resource Rooms is necessary to serve more deaf students, especially in the rural area of the Municipality. Based on the data, we show that the municipality of Igarapé-Miri has few regulations that address the education of the deaf, however it is necessary to be aware of the school “inclusion” policies for the deaf as education is a dynamic process and demands new organizations and local actions in the face of new questions from the deaf. Because the existence of legislation serves as an expansion of the possibility against exclusion.